Impact of the COVID-19 pandemic on audiology services in South Africa: A preliminary study - Katerina Ehlert (AOSIS, 2023)
Background: Hygiene-, work practices, travel, personal interactions and access to healthcare services changed for the majority of the world during the pandemic. Aim: This study aimed to discover the knowledge, impact and attitudes towards COVID-19 on the professional practices of public and private sector audiologists in South Africa. Setting: The study included 76 audiologists registered with the Health Professions Council of South Africa (HPCSA) and employed in the public, educational, tertiary or private practice and private sector in South Africa. Methods: A cross-sectional self-administered electronic survey study design was implemented. Results: Audiologists had appropriate knowledge regarding COVID-19. During hard lockdown, 69% of respondents saw less than 40% of their usual patient load, only 31% saw 60% - 100% of their usual patient load. During lower lockdown levels, majority of respondents (73.7%) saw 60% - 100% of their patient load while 26.3% still saw less than 40% of their usual patient load. Only hearing aid reprogramming, hearing aid trouble shooting, cochlear implant pre-counselling and adult hearing screening could be offered via tele-audiology. The main challenges faced were fear of infection, infection control measures in the workplace, accessibility and limited services provided during the various lockdown levels. Conclusion: The pandemic and lockdown levels had a definite impact on audiological service provision and many adaptations regarding service delivery and infection control in the workplace were required. Contribution: The relevance of this work for health services is the identification of the challenges experienced by audiologists during the pandemic and the opportunities to prepare for the future.